PENERAPAN TQM (TOTAL QUALITY MANAGEMENT) DALAM MENINGKATKAN KINERJA PERUSAHAAN UMKM - Ari Zaqi Al Faritsy (Kompetensi (Competence : Journal of Management Studies), 2014)
Improving the performance of the company can be done by implementing total quality management (TQM), which according to Silaetal (2007) Total quality management plays a very important role in increasing the strength of the company's competitiveness. Good performance of the company will be able to compete with other companies in improving the quality of the product. In addition, TQM is one of the best management practices in companies that emphasize the overall quality paradigm in the company. These researches analyze the application of TQM in UMKM Aksis Jaya and see the effect of the ten characteristic of TQM on firm performance by using multiple linear regression analysis. In addition,the proposed improvements that needs to be done to improve the performance of the company. Characteristic TQM that has been implemented in UMKM Aksis Jaya is focused on the customer, obsession with quality, teamwork, controlled freedom, unity of purpose and the involvement and empowerment of employees. While characteristic that have not been applied is a scientific approach, the long-term commitment, continuous improvement systems and education and training. Improvements need to be made to reduce waste in the work area by promoting cleanliness, neatness and discipline in work, making SOP, documentation of data, and build a culture of continuous improvement. TQM implementation provides significant influence on increasing the performance of the company (F count 2,145 lebih dari F table 0.360).